VIRUS — A Laboratory Information System for Clinical Virology - Blomberg, J.; Mattson, J.; Börjesson, B.; Hast, S.; Andersson, P.; Holm, K. (Methods of Information in Medicine, 1979)
A system covering request registration, analytical orders, printing of worksheets, result reporting, result control and printing of patient reports is presented. Additionally, interim reports can be produced; accounting is automatic, and group requests and requests for new analyses of old samples can be handled. The system meets the demand for retrospective analysis which arises when acute intermediate and convalescent sera have to be analyzed simultaneously. Consequently, results from the same type of analysis performed on the same sample on different occasions can be handled and presented in a clear way on the VDU and on the report.All work is performed on-line in real time via VDU screens. All data are stored on a 3 x 100 Mbyte disk chive which can accommodate approximately 6 years’ work.The system has been implemented as a terminal system with 5 VDU: s and one line printer connected to an IBM 370/158 computer. The IMS data base management system has been utilized.
Keywords: Virology; On-line Information; Databank; Immunity